Health economic evaluation of self-injection of biologics in patients with rheumatoid arthritis using a Japanese real-world web-based survey - Kazuhiko Takahata; Yui Maeda; Eiichi Tanaka; Ryoko Sakai; Manabu Akazawa (BMC Health Services Research)
Abstract Background Biological disease-modifying antirheumatic drugs (bDMARDs) have dramatically improved the quality of life of patients with rheumatoid arthritis (RA); however, concerns regarding their high cost persist. Self-injection (SI) may reduce medical expenses by decreasing the frequency of hospital visits. In this study, we compared the health economic costs of patients with RA who selected SI of bDMARDs and those who did not. Methods In this cross-sectional study, we analyzed data from January 2024 using a web-based self-report survey provided by Medilead, Inc. This study included patients with RA who were divided into the SI and non-SI groups. We calculated per visit and total annual out-of-pocket medical expenses for each group. Results Among 326 patients with RA, 79 (24.2%; female: 64.6%; mean age: 60.2 years) were treated with bDMARDs. Of these, 65 patients (82.3%) selected SI, and 14 (17.7%) selected non-SI administration. The non-SI group had a higher median frequency of hospital visits than the SI group (12 vs. 6 visits per year). The median out-of-pocket medical expense per visit was higher in the SI group (155.17 USD/visit) than in the non-SI group (86.21 USD/visit). However, the SI group had lower total annual out-of-pocket medical expenses than the non-SI group (948.42 USD/year vs. 1,071.72 USD/year, respectively). Conclusion Over 80% of patients with RA selected SI to administer bDMARDs, and their total annual out-of-pocket medical expenses were lower than those of patients who selected non-SI owing to the reduced frequency of hospital visits. The results of our study may provide useful insights into the selection of self-injectable bDMARDs for therapeutic decision-making based on out-of-pocket medical expenses.